IgY extraction and purification from chicken egg yolk - BIZANOV, G (Journal of the Hellenic Veterinary Medical Society, 2018)
The interest for immunoglobulin Y (IgY) isolation arises from the possible applications of these immunoglobulins in diagnostics and therapeutics. Powered whole eggs or yolks have been used in veterinary medicine as an inexpensive immunoglobulin Y source for the treatment of enteric diseases. Incorporating feed grade egg yolk antibodies into animal diets has been examined extensively in an attempt to limit pathogenic diarrhea causing by Escherichia coli in swine, and limit Salmonella establishment in calves and mice, as well as Campylobacter, Clostridium, and Salmonella in poultry. Thus, therapeutic administration of the IgY might reduce the clinical use of antibiotics, and minimize the risk of developing bacterial antibiotic resistance. Methods of immunoglobulins isolation and purification from hen yolk are reviewed. For a large-scale production, one of the problems is separating the water-soluble protein fraction from the lipids and other hydrophobic substances. Precipitation or aggregation of lipid occurs under various conditions: (1) by use of water dilution under acidic conditions; (2) by means of acids; (3) combination of solvents (chloroform, aceton) which selectively solubilize the lipids; (4) using of 3.5% polyethylene glycol and (5) by applying natural gums (polyanionic polysaccharides). Further purification of IgY after crude extraction can be achieved by selective precipitation. IgY precipitation can be carried out by salt precipitation using saturated solutions of sodium or ammonium sulphate, which dehydrate proteins. Furthermore, selective precipitation is achieved by using 8.8% sodium chloride or at 12% of polyethylene glycol. The methods comparison on the basis of IgY yield, showed that the mean IgY yield obtained by water dilution method or precipitation with salts, or by using polyethylene glycol was 5.6 mg/ml of egg yolk, 6.3 mg/ml of egg yolk and 8.7 mg/ml of egg yolk correspondingly and did not significantly differ between them. Water dilution method seemed to offer the best IgY recoveries. Moreover, this method in combination with chromatography and filtration can be applied easily in an industrial environment. Filtration technology offers the best opportunities for industrial applications while precipitation with polyethylene glycol or salts provides a cheap and easy methodology for laboratory use. In the production of safer foods, an important strategy is to exploit natural antimicrobial agents as alternatives to conventional synthetic chemical preservatives. In this regard, the IgY is of much interest for its potential application in fortified foods, such as administration for prevention of enteric diseases. The use of IgY is cost-effective.